Hybrid Approach for Moving Object Detection in Video Surveillance System - Lavanya, PL.D.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
Object tracking detection plays a vital role in videosurveillance system. It is mainly focused in banks, teleconferencing, shopping and traffic monitor system. Objecttracking is the process of detecting objects which is moving insequences frames of a video, to detect the moving objects,different techniques are used such as background subtraction,optical flow, GMM(Gaussian Mixture Model). The mainobjective of the proposed work is to detect the moving objectswith less complexity and accuracy using frame differencingmethod. First background subtraction is detected using recursivetechnique. Then noises are removed by wiener filter and YCbCrColor space for foreground object. In order to obtain accuratedetection, shape based image retrieval technique is used. Finallythe experimental results show that this method can reducecomplexity and generate accurate image without any noises.